Neonatal vaccination under present-day conditions: Relevance and safety - N. V. Bashmakova (Rossijskij Vestnik Perinatologii i Pediatrii, 2016)
The paper reviews the recent literature on vaccination against hepatitis В virus in the first 24 hours and on that against tuberculosis on 3—7 days of fife in all newborns, if not contraindicated. The question arises acutely as to how to organize effective vaccination in obstetric care facilities that concentrate high perinatal risk patients. Moreover, unfavorable external and internal factors change babies' immunobiological responsiveness — this cannot fail to affect the course of a vaccination process. Obviously, the tactics of im-munoprophylaxis in children with health problems should be individualized and include efforts to enhance the efficiency of vaccination and prevent possible complications.